Determination of toxicity and antioxidants on white edible bird nest (Aerodramus fuciphagus) from different district in Kelantan - Shaheran, Anish Ameera (2018)
Edible bird nest (EBN) is one of the natural products that have high therapeutic potential and pharmacological properties. Therefore, this study aimed to determine the toxicity and antioxidants activity on white edible bird nest (Aerodramus fuciphagus) from different district in Kelantan (Tanah Merah, Tumpat and Jeli). The samples were extracted using three solvents which are distilled water, sodium hydroxide and hydrochloric acid. The toxicity of the EBN samples with different solvent of extraction were tested using MTT assay against cancerous (HeLa and MCF-7) and non-cancerous cell line (SVG p12). Minerals content in EBN was studied using inductively couple plasma mass spectrometry (ICP-MS) and the other toxicity test was brine shrimp lethality assay (BSLA) for LC50 values. The antioxidants activity was tested on EBN samples extracts using DPPH radical scavenging assay and Ferric reducing power assay (FRAP). EBN samples extracts showed higher inhibition activity against MCF- 7 cell line. Meanwhile, three samples of EBN extracts induced cell proliferation on SVG cell line as the IC50 value more than 100%. Minerals content in all EBN samples were below the maximum regulatory limit as suggested by FDA, WHO and SIRIM guidelines except sodium content that slightly higher than 2 ppm. The results showed no LC50 value was determine on EBN against brine shrimp. The antioxidants activity using DPPH and FRAP assay showed that NaOH extracts from three sample EBN had the lowest IC50 values and the highest reducing power. Thus, the results finding showed that the EBN samples extracts can be considered as cancer-preventive agents and are relatively safe to be consumed. Extracts of EBN samples can be considered asantioxidants agent. However, further validation have to be performed to understand the active compounds that poses safety, toxicity and antioxidants activity of EBN.